2020
DOI: 10.1186/s13063-020-04716-1
|View full text |Cite
|
Sign up to set email alerts
|

A three-arm, multicenter, open-label randomized controlled trial of hydroxychloroquine and low-dose prednisone to treat recurrent pregnancy loss in women with undifferentiated connective tissue diseases: protocol for the Immunosuppressant regimens for LIving FEtuses (ILIFE) trial

Abstract: Background Undifferentiated connective tissue disease (UCTD) is known to induce adverse pregnancy outcomes and even recurrent spontaneous abortion (RSA) by placental vascular damage and inflammation activation. Anticoagulation can prevent pregnancy morbidities. However, it is unknown whether the addition of immune suppressants to anticoagulation can prevent spontaneous pregnancy loss in UCTD patients. The purpose of this study is to evaluate the efficacy of hydroxychloroquine (HCQ) and low-dose prednisone on r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Previous studies reported that recurrent miscarriage was related to rheumatoid immune-related diseases, such as undifferentiated connective tissue diseases, antiphospholipid syndrome, antinuclear autoantibodies (24)(25)(26). Our previous study also found that mixed lymphocyte reaction-blocking factors is related to high expression of some rheumatoid biomarkers (27).…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies reported that recurrent miscarriage was related to rheumatoid immune-related diseases, such as undifferentiated connective tissue diseases, antiphospholipid syndrome, antinuclear autoantibodies (24)(25)(26). Our previous study also found that mixed lymphocyte reaction-blocking factors is related to high expression of some rheumatoid biomarkers (27).…”
Section: Discussionmentioning
confidence: 50%
“…It was shown that pregnancy and puerperium may trigger disease flares and evolution to a definite CTDs ( Castellino et al, 2011 ; Yang et al, 2020 ). Severe disease activity was reported in about 2% of pregnant women with UCTD, which typically show a more benign course compared to other CTDs, such as SLE ( Kaufman et al, 2021 ).…”
Section: How Pregnancy Can Affect the Disease Course?mentioning
confidence: 99%
“…Moreover, endothelial dysfunction ( Laczik et al, 2014 ) and cytokine imbalance ( Nakken et al, 2015 ) were found in pregnant women with UCTD, playing a role in causing defective placentation. Therefore, ANA and inflammation may affect platelet function, imbalance coagulation/anticoagulation mechanisms promoting a prothrombotic state, cause endothelial dysfunction and, ultimately, may impair spiral arteries remodeling and placenta development, increasing the risk of PE, FGR, SGA and RPL in pregnant women with UCTD ( Yang et al, 2020 ).…”
Section: How Uctd Can Affect Pregnancy Outcomes?mentioning
confidence: 99%
See 2 more Smart Citations